Phytochemical screening and antibacterial activity of Skimmia anquetilia N.P. Taylor and Airy Shaw: A first study from Kashmir Himalaya - Nabi, Masarat; Tabassum, Nahida; Ganai, Bashir Ahmad (Frontiers in Plant Science, 2022)
The present study was aimed to explore the antibacterial activity of various organic root extracts of Skimmia anquetilia N.P. Taylor and Airy Shaw and the identification of major functional groups and phytoconstituents through Fourier transform infrared spectrometer (FTIR) and Gas chromatography-mass spectrometer (GC-MS). The extracts were evaluated for antibacterial activity against multidrug-resistant (MDR) strains viz, Pseudomonas aeruginosa (MTCC424), Escherichia coli (MTCC739), Klebsiella pneumoniae (MTCC139), Salmonella typhi (MTCC3224), and Staphylococcus aureus (MTCC96). ESKAPE pathogens such as Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas aeruginosa are responsible for a majority of all healthcare acquired infections. The ethyl acetate extract showed the highest zone of inhibition against P. aeruginosa (18 mm) followed by S. aureus (17 mm). The minimum inhibitory concentration (MIC) of ethyl acetate extract against strain of S. aureus (4 mg mL-1) demonstrated therapeutically significant antibacterial activity. The FTIR spectra of root extracts revealed the occurrence of functional characteristic peaks of alcohols, carboxylic acids, aromatic compounds, alkanes, alkenes, and amines indicates the presence of various metabolites in the extracts. The GC-MS investigation led to the identification of diverse phytoconstituents in each of the extracts with varying concentrations and molecular masses. The highest number of compounds were isolated from methanol extract (112), followed by n-hexane extract (88), and ethyl acetate extract (74). The most predominant compounds were 5, 10-pentadecadien-1-ol, (Z,Z)- (33.94%), n-hexadecanoic acid (13.41%) in n-hexane extract, 5,10-pentadecadien-1-ol, (Z,Z)- (10.48%), 1-hexyl-2-nitrocyclohexane (7.94%) in ethyl acetate extract, and 1-hexyl-2-nitrocyclohexane (15.43%), cis,cis,cis-7,10,13-hexadecatrienal (13.29%) in methanol extract. The results of the present study will create a way for the invention of plant-based medicines for various life-threatening microbial infections using S. anquetilia, which may lead to the development of novel drugs against drug-resistant microbial infections.